Physical Methods for Assessing the Load of Friction Pairs of Braking Devices (Part II) - Zhuravlev, D.Yu.; Javadov, M.Y.; Skrypnyk, V.S.; Volchenko, N.A.; Krasin, P.S.; Evchenko, A.S. (Herald of Azerbaijan Engineering Academy, 2022)
In the first part of the paper, the attention is given to the main principles of the physical methods, as well as the "mechanical-thermal" loading of friction pairs of braking devices. In the second part of the paper, the analysis of principles is conducted and their impact on the energy fields of the brake friction pairs are illustrated. Based on the operation of the principles, the following energy fields are distinguished in pairs: "electric-heat," "chemical-thermal", and "electromagnetic". The "electric heat field" is based on the contact-pulse interaction of micro-protrusions of friction surfaces with various gradients of electrical potential and temperature under given boundary conditions. The "chemical-thermal" field rests on the model of a double electric layer in a pair of brake friction. The "electromagnetic" field is associated with a harmonic variable external electric field. Let us give an analysis of all energy fields.